Respuesta :

3m + 2p = 1.8 ⇒ 9m + 6p = 5.4
4m + 6p = 2.9 ⇒ 4m + 6p = 2.9
                                    5m = 2.5
                                     5       5
                                      m = 0.5
                            3m + 2p = 1.8
                       3(0.5) + 2p = 1.8
                           1.5 + 2p = 1.8
                         - 1.5          - 1.5
                                    2p = 0.3
                                     2       2
                                       p = 0.15
                                (m, p) = (0.3, 0.15)